IMPLEMANTASI KETELADANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER ISLAMI SISWA KELAS VIII A DI SMP NEGERI 1 SAMBAS - Agustiadi Agustiadi (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2013)
The purpose of this research is to reveal about: 1) Islamic character of class VIII A students at SMP Negeri 1 Sambas, 2) PAI teacher exemplary in shaping Islamic character in VIII A grade students at SMP Negeri 1 Sambas, 3) The exemplary role of PAI teachers in shaping Islamic character in class VIII A at SMP Negeri 1 Sambas 4) Supporting and inhibiting factors in providing exemplary to VIII A grade students at SMP Negeri 1 Sambas. The research uses descriotive research with a qualitative approach. Data collection techniques using interviews dan documentation. As for the data analysis techniques used are data reduction, data display, and conclusions. The results of this study show: 1) Islamic religious education teachers in instilling Islamic character in class VIII A students by applying (a) The culture of shaking from the culture of shaking will create Islamic characters namely friendship between teacher and students. (b) Habituatoin carriad aut by Islamic religious teachers and students, and (c) Islamic religious education teachers also apply honesty, courtesy and responsibility in class VIII A. The application has a possitive impact between teachers and students. 2) The exemplary role of the Islamic religuous educatoin teacher in shaping Islamic character in class VIII A students at SMP Negeri 1 sambas first forms their own porsonality in the, reality of students’ view that all the actions done by the teacher are good, then students become teachers as exampless or role models to be imitated by students imitate everything that is in the teacher itself such as attitudes, speech styles, behavior, actions and clother used. 3) the exemplary role of Islamic education teachers is very influential in shaping the Islamic charakter of students. When teaching Islamic religious education teachers, especially in class VIII A, namey: (a) Guiding, (b) Teaching, and (c) Training, children to gain skills, knowladge, abilities, good behavior, and good manner. 4) Supporting faktors in providing exemplary to students cannot be sapparated from the behavor or personality of the teachers and the facilities and infrastructure that can be used by PAI teschers to support or provide exemples. Inhiting factors in giving exemples to students, namely from the influence of poor friends and influences from outside the school.